Save Environment by Replace Plastic, The Case of PepsiCola - Yee, Foo Yuen; Kee, Daisy Mui Hung; Jye, Lum Mei; Jingyi, Low; Wen, Lim Jia; Almutairi, Shahad (AIBPM Publisher, 2020)
Pepsi-Cola is one of the largest multinational food and beverage brand in the world. In 1902 Pepsi-Cola Company was founded in the United State. It has continuously developed during the past 118 years. Our Report is about replacing Plastic bottle to Reusable Plastic to develop and change the company product to be better. The issue of environmental pollution especially plastic pollution is becoming serious; it is damaging the ecological environment. This had triggered the attention of organization on the environment and some of them take their responsibility to work hard on sustainability a strong environmental profile.